Gabon : First Review Under the Stand-By Arrangement and Requests for Waiver of Nonobservance of Performance Criteria and Modification of a Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Gabon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Gabon showed robust economic growth, low inflation, and large fiscal savings from high oil revenue, underpinned by prudent macroeconomic policies and structural reforms under the Stand-By Arrangement (SBA). Executive Directors suggested that stronger fiscal discipline is essential to keep the economy stable. They stressed the need for strengthening public financial management and adjusting fiscal programs to accommodate higher-than-programmed fuel subsidies. They advised that enhancing the investment climate by strengthening governance and increasing transparency, as well as by lifting the temporary price controls, will remove constraints to the growth of non-oil activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet